Policies for Livestock Development in the Ethiopian Highlands - Benin, Samuel; Ehui, Simeon; Pender, John L. (International Food Policy Research Institute, 2006)
Livestock have diverse functions for the livelihood of farmers in mixed croplivestock systems in the highlands of East Africa. Livestock provide food in the form of meat and milk, nonfood items such as draft power, manure, and transport services as inputs into food crop production, and fuel for cooking. Livestock are also a source of cash income through sale of the above items, animals, hides, and skins. Furthermore, they act as a store of wealth and determine social status within the community. Because of these important functions, livestock play an important role in improving food security and alleviating poverty. Because they are central to nutrient cycling, livestock are important to the efficiency, stability, and sustainability of farming systems in the East African highlands (Ehui et al. 1998). The International Livestock Research Institute (ILRI) and its partners and collaborators have shown that securing the current and future livestock assets of the poor is a major pathway to get the rural poor out of the poverty spiral (ILRI 2002).